DETERMINATION OF PHYSICAL AND BIOMETRIC PROPERTIES OF ONION BULBS IN RELATION TO DESIGN OF DIGGER CUM WINDROWER - SHIDDANAGOUDA YADACHI; KIRAN NAGAJJANAVAR (The Bioscan, 2020)
The physical and biometric properties play vital role in design of any soil operating machine. In view of designing the various components of digger-cum-windrower, physical and biometric properties were determined for three varieties of onion bulbs. The critical dimensions, viz. equatorial diameter, polar diameter, thickness, geometric mean diameter, arithmetic mean diameter, cross sectional area, shape index, bulk density, true density, weight of bulb, angle of repose were determined. Geometric and arithmetic mean diameters were identical for all three varieties, which could help designing soil separator effectively. The Arka Bhim was observed to be denser than that of two other varieties. The maximum cross sectional area was recorded for both Arka Kalyan and N 53 (1.74±0.05 cm 2 and 1.75±0.07 cm 2 ) against Arka Bhim (1.50±0.04 cm 2 ). Highest values of true density and bulk density were recorded for Arka Bhim. Shape index was under 1.5 for all the three varieties and bulb was considered to be nearly spherical. The Arka Bhim with its maximum frictional coefficient experienced less flow behavior. The measured properties as a whole helped optimizing design values of different components and effective fabrication of prototype.